P594 Bowel ultrasound is useful in predicting relapse in patients with Ulcerative Colitis in remission. (30th January 2023) - Maeda, M; Sagami, S; Tashima, M; Yamana, Y; Karashima, R; Miyatani, Y; Hojo, A; Nakano, M; Hibi, T; Kobayashi, T
Abstract: Background: Endoscopic remission is associated with better long-term outcomes of ulcerative colitis (UC), and therefore, it is considered a treatment target. However, endoscopy is invasive and frequent monitoring is not feasible. We have reported that bowel ultrasound (BUS) is useful in predicting endoscopic and histologic severity and in determining response to treatment (Sagami S et al, APT 2020 & 2022). However, it is unclear whether BUS can predict the relapse of UC in remission. Methods: We conducted a retrospective cohort study enrolling UC patients who underwent BUS from Jul 2018 to Jul 2021 during clinical remission (Patient Reported Outcome-2 ≦ 1 and no rectal bleeding) for at least 3 months and followed for 1 year. Spearman rank correlation coefficient was used to analyse the correlation between BUS and Mayo endoscopic subscore (MES) (evaluation of the most severe part of the colon). The association between BUS findings (bowel wall thickness (BWT), bowel wall flow (BWF), bowel wall stratification (BWS), enlarged lymph nodes), Milan Ultrasound Criteria (MUC = 1.4 × colonic BWT + 2 × colonic BWF (0 = absence, 1 = presence of colour Doppler signal)) (Allocca M et al, UEGJ 2021), MES, CRP and faecal calprotectin (FC) and subsequent clinical relapse was evaluated. Relapse was defined as rectal bleeding score ≧ 1, stool frequency score ≧ 2, or treatment intensification for symptoms. Results: A total of 58 patients were included in the study. The median age was 46 years, 37 (63.8%) were male, 39 (67.2%) were pancolitis, and the median disease duration was 116 months. BWT and BWF were moderately correlated with MES but MUC showed a numerically highest coefficiency (0.61) when evaluated for the colon. Overall, 18 patients (31.0%) relapsed within 1 year. Neither BWT, BWF, BWS, enlarged lymph nodes, nor CRP was predictive for relapse. The log-rank test showed MUC > 6.2 (p = 0.019), MES ≥ 1 (p = 0.013), and FC ≥ 250 μg/g (p = 0.040) were associated with a shorter time to relapse. Cox proportional hazards model showed MUC > 6.2 (HR 3.22: 95%CI 1.14-9.08, p = 0.027), MES ≥1 (HR 8.70: 95%CI 1.11-68.1, p = 0.040) had a higher risk of relapse in 1 year. Sensitivity, specificity, PPV, and NPV of MUC > 6.2 for relapses of different time points (3, 6, and 12 months) showed high specificity of 0.90-0.91 and NPV of 0.74-0.90. Interestingly, 4 out of 9 patients with MUC > 6.2 relapsed within 3 months, suggesting MUC > 6.2 is a risk of short-term relapse. Conclusion: BUS in UC patients in remission can predict relapse using MUC. In particular, the MUC score ≤ 6.2 is associated with a lower risk of relapse and could be a treatment-target alternative to endoscopic healing.